Differences between diabetic and non-diabetic patients with community-acquired pneumonia in primary care in Spain - Arias Fernández, Loreto (BMC Infect Dis, 2019)
BACKGROUND: Diabetes is one of the underlying risk factors for developing community-acquired pneumonia (CAP). The high prevalence of diabetes among population and the rising incidence of this illness, converts it as an important disease to better control and manage, to prevent its secondary consequences as CAP. The objective of this research is to describe the characteristics of the patients with diabetes and the differences with the no diabetes who have had an episode of CAP in the context of the primary care field. METHODS: A retrospective, observational study in adult patients (> 18 years-old) who suffer from CAP and attended at primary care in Spain between 2009 and 2013 was developed using the Computerized Database for Pharmacoepidemiological Studies in Primary Care (BIFAP). We carried out a descriptive analysis of the first episodes of CAP, in patients with or without diabetes as comorbidity. Other morbidity (CVA, Anaemia, Arthritis, Asthma, Heart disease, Dementia, Depression, Dysphagia, Multiple sclerosis, Epilepsy, COPD, Liver disease, Arthrosis, Parkinson’s disease, Kidney disease, HIV) and life-style factors were also included in the study. RESULTS: A total of 51,185 patients were included in the study as they suffer from the first episode of CAP. Of these, 8012 had diabetes as comorbidity. There were differences between sex and age in patients with diabetes. Patients without diabetes were younger, and had less comorbidities including those related to lifestyles such as smoking, alcoholism, social and dental problems than patients with diabetes. CONCLUSIONS: Patients who developed an episode of CAP with diabetes have more risk factors which could be reduced with an appropriate intervention, including vaccination to prevent successive CAP episodes and hospitalization. The burden of associated factors in these patients can produce an accumulation of risk. Health care professional should know this for treating and control these patients in order to avoid complications. Diabetes and those other risk factors associated could be reduced with an appropriate intervention, including vaccination to prevent the first and successive CAP episodes and the subsequent hospitalization in severe cases.